Exosomes Derived From Umbilical Cord Mesenchymal Stem Cells Treat Cutaneous Nerve Damage and Promote Wound Healing - Zhu, Ziying; Zhang, Xiaona; Hao, Haojie; Xu, Heran; Shu, Jun; Hou, Qian; Wang, Min (Frontiers in Cellular Neuroscience, 2022)
Wound repair is a key step in the treatment of skin injury caused by burn, surgery and trauma. Various stem cells have been proven to promote wound healing and skin regeneration as candidate seed cells. Therefore, exosomes derived from stem cells are emerging as a promising method for wound repair. However, the mechanism by which exosomes promote wound repair is still unclear. Here, we report that exosomes derived from umbilical cord mesenchymal stem cells (MSC-Exo) promote wound healing and skin regeneration by treating cutaneous nerve damage. The results revealed that MSC-Exo promote the growth and migration of dermal fibroblast cells. In vitro culture, dermal fibroblasts could differentiate to nerve cells and secrete nerve growth factors when stimulated by exosomes. During the repair process in vivo, the MSC-Exo accelerated the recruitment of fibroblasts at the site of trauma and significantly enhanced cutaneous nerve regeneration. Interestingly, it was found that MSC-Exo could promote wound healing and skin regeneration by recruiting fibroblasts, stimulating them to secrete nerve growth factors (NGF), and promoting skin nerve regeneration. Therefore, we concluded that MSC-Exo promote cutaneous nerve repair, which may play an important role in wound repair and skin regeneration.